2017
DOI: 10.19183/how.24.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Test Results: An Opportunity for English Program Improvement

Abstract: This case study explores the relationship between the results obtained by a group of Industrial Engineering students on a national standardized English test and the impact these results had on language program improvement. The instruments used were interviews, document analysis, observations, surveys, and test results analysis. Findings indicate that the program has some weaknesses in terms of number of hours of instruction, methodology, and assessment practices that affect the program content and the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…They explicitly focused on the structure of sentences and translated them into Spanish due to the students' target language low proficiency. This panorama has not changed much since, according to some studies, English language teaching at some universities in Colombia is focused mainly on grammar instruction (Jiménez et al, 2017;Pavas-Amado, 2017;Sánchez-Solarte et al, 2017). Finally, it was also evidenced that they taught language skills separately placing major emphasis on writing and reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They explicitly focused on the structure of sentences and translated them into Spanish due to the students' target language low proficiency. This panorama has not changed much since, according to some studies, English language teaching at some universities in Colombia is focused mainly on grammar instruction (Jiménez et al, 2017;Pavas-Amado, 2017;Sánchez-Solarte et al, 2017). Finally, it was also evidenced that they taught language skills separately placing major emphasis on writing and reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that deal with teaching methodologies and practices in the efl arena including influential teaching factors and error correction approaches. In Colombia, recent studies have found that English language teaching at some universities is dominated by some methodologies focused mainly on grammar instruction (Jiménez et al, 2017;Pavas-Amado, 2017;Sánchez-Solarte et al, 2017). Perhaps one exception to such tendency was identified by Posada-Ortiz and Patiño-Garzón (2007), who studied the efl teaching methodology at Universidad del Valle and found that it was based on cooperative learning and the communicative approach.…”
Section: Teachers' Methodological Practices In Efl Education At Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The English Center offers a program of six levels of English directed to students from different Faculties, and all teachers must follow the same curriculum which is mostly grammar-based, according to Level Fourth syllabus, at the end of the semester students should be able to: apply critical thinking, use English to solve problems related to the students' major, choose the best resources in problem solving, express ideas, opinions, and feelings adequately, design their critical thinking process in their learning habits, and discuss current, national and international events related to the major. Furthermore, the Article 34 of the Academic Regulation Regimen states that students must demonstrate their outcome by taking a proficiency test once they have approved 60% of their career program (Jiméneza, Rodríguez, & Rey, 2017).…”
Section: Educación Inclusivamentioning
confidence: 99%
“…Por otra parte, en el documento "Standardized test results: an opportunity for English program improvement", de Jiménez, Rodríguez & Rey (2017), se presenta un estudio de caso, en el cual se analizan los resultados de la competencia genérica de inglés en las Pruebas Saber Pro, de algunos estudiantes de Ingeniería Industrial; lo anterior, con el fin de lograr establecer estrategias de mejora y toma de decisiones en el programa de Inglés de la Universidad Simón Bolívar, Colombia. Jiménez et al (2017) hacen hincapié en la ausencia de estudios sobre las Pruebas Saber Pro en Colombia, sin embargo, rescatan que tanto las políticas públicas implementadas como los esfuerzos realizados desde el Ministerio de Educación Nacional y las Instituciones de Educación Superior, han fortalecido la importancia de esta prueba estandarizada. Con el propósito de lograr el objetivo planteado en el artículo, Jiménez et al (2017) parten de la definición de evaluación, explicando esta como un proceso que retroalimenta la toma de decisiones, y no tan solo como un fin.…”
Section: Específicas Competencias Específicas | Revista Virtualunclassified